PENGEMASAN PAKET WISATA BERBASIS BUDAYA DENGAN PEMANFAATAN MODA TRANSPORTASI TRADISIONAL ANDONG DI KOTA YOGYAKARTA - Wicaksono, Raden Ichlasul Zinedine Bieldam; Sagita, Putu Agus Wikanatha; Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 1 (2022): Jurnal IPTA (July 2022)DO - 10.24843/IPTA.2022.v10.i01.p04, 2022)
Yogyakarta is the largest number of tourists in DIY Province. Focuses of tourism development sector is cultural tourism, one of the cultures owned by the city of Yogyakarta is andong traditional transportation which is starting to lose competition with modern transportation. Currently, Yogyakarta Tourism Department is focusing on increasing the number of visits and length of stay of tourists with various efforts, which is tour packages. Therefore, the packaging of cultural tourism packages using andong needs to be done to anticipate the problems of traditional transportation and to increase the number of tourist visits. Data collection techniques used are observation, interviews, documentation and literature study. Informant determination technique used was purposive sampling with Tourism Department and Transportation Department of Yogyakarta as base informant and Andong DIY Association and manager of cultural tourism destinations as key informants. Analytical technique used is descriptive qualitative. Based on the research results, the city of Yogyakarta has the potential for cultural tourism in 5 indicators such as arts exhibition (Keraton Yogyakarta), arts (Taman Pintar and Sonobudoyo Museum), festivals (Tuesday Wage Art Festival), traditional food (Gudeg Yu Djum and Bakpia Pathok 25) and history (Fort Vredeburg Museum and Taman Sari). Andong has important components in packaging tour packages such as conditions and facilities, price/cost, time, location, accessibility and uniqueness. The potential for cultural tourism will be packaged by 3 tour packages, namely Chronicle of Kasultanan Ngayogyakarta, Art of Yogyakarta and Countdown Tuesday Wage. The package lasts for halfday and will be managed by Andong DIY Association.